Estimating potential trade links in the international crude oil trade: A link prediction approach. (1st May 2016) - Guan, Qing; An, Haizhong; Gao, Xiangyun; Huang, Shupei; Li, Huajiao
Abstract: Estimating potential trade links is essential for exploring the information implied by international crude oil trade data, which contain obvious trade links among countries. In addition, it is important for governments to assess the evolution trend of international crude oil trade in order to avoid trade risk. This study introduces the link prediction approach to explore potential trade links from the perspective of relations based on the topological attributes of countries. We take the number of common trade partners for each country pair as the potential linking motivation. Based on this, we confirm this as a general feature for most existing trade links and thereby describe the real distribution of trade relations. Furthermore, our study analyzes the practical meanings of explored potential trade links with considerations of countries' crude oil trade roles. We find that the number of common trade partners is indeed one of the structural linking motivations in international crude oil trade. It can not only represent the possibility of trading relations, but also reflect the competition among countries. By using this evaluation index, we then estimate potential trade partners combined with countries' crude oil trade roles and provide suggestions for governments about future trading strategies. Highlights: Implied trade relationships are explored as potential trade links. This study introduces the link prediction approach to assess potential trade links. High number of common neighbors is general for most existing trade links. Common trade partners for each country pair are a potential linking motivation. Potential trade links are estimated by our study for certain pairs of countries.